Estimation of the in-vivo minimum inhibitory concentration of cipargamin in uncomplicated Plasmodium falciparum malaria - Tinh Tran, H; White, N; Thanh Nguyen, T; Toa Nhu, H; Duc Phung, T; Tarning, J; Nosten, F; Magnusson, B; Prakash Jain, J; Hamed, K (American Society for Microbiology, 2016)
The minimum inhibitory concentration (MIC) of an antimalarial drug for a particular infection is the drug level associated with a net parasite multiplication rate of one per asexual cycle. To ensure cure of malaria the MIC must be exceeded until all parasites have been eliminated. The development of highly sensitive and accurate polymerase chain reaction quantitation of low-density malaria parasitemia enables prospective pharmacokinetic–pharmacodynamic (PK–PD) characterization of antimalarial drug effects, and now allows identification of the in-vivo MIC. An adaptive design and PK–PD modeling approach was used to determine prospectively the MIC of the new antimalarial cipargamin (KAE609) in adults with uncomplicated Plasmodium falciparum malaria, in an open-label, dose-ranging phase 2a study. Vietnamese adults with acute P. falciparum malaria were allocated sequentially to treatment with single 30 mg (n = 6), 20 mg (n = 5), 10 mg (n = 7), or 15 mg (n = 7) doses of cipargamin. Artemisinin-based combination therapy was given after parasite densities had fallen and then risen as cipargamin levels declined below the MIC, but before a return of signs or symptoms. The rates of parasite clearance were dose-dependent with near saturation of effect at an adult dose of 30 mg. The developed PK–PD model accurately predicted the therapeutic responses in 23/25 patients. The predicted median in-vivo MIC was 0.126 ng/mL (range 0.038–0.803 ng/mL). Pharmacometric characterization of the relationship between antimalarial drug concentrations and parasite clearance rates following graded sub-therapeutic antimalarial drug dosing is safe, and provides a rational framework for dose-finding in antimalarial drug development.